Depression and dementia: differentiation and comorbidity - V. Yu. Lobzin; A. Yu. Emelin (Неврология, нейропсихиатрия, психосоматика, 2020)
The relationship between cognitive impairment (CI) and depression is complicated: h\the latter can be one of the symptoms of Alzheimer’s disease or may precede the onset of CI. Depression also has cognitive symptoms that alter the clinical presentation of the disease. Patients with depressive pseudodementia experience difficulties concentrating, confusion concurrent with impaired memory and thinking, whereas the patient’s answers to certain questions often resemble the vague pseudoamnestic pattern of the impairment. Mnestic disorders occur in at least 40% of patients with depression, and if the latter is diagnosed in the patient who already has dementia, the rate of cognitive decline may be faster. The mechanisms underlying the development of CI can also affect the development of depression. When assessing the risk of dementia in depression, it is necessary to take into account the time from the onset of a major depressive episode until moderate CI appears, to carry out a detailed analysis of neuropsychological testing for Alzheimer’s disease and to use the current lifetime markers for amyloidosis and neurodegeneration. Serotonergic antidepressants and non-pharmacological cognitive behavioral and psychotherapeutic procedures play the most important role in the treatment of depression and dementia.